Pengaruh Dukungan Sosial Teman Sebaya dan Kedisiplinan Belajar Terhadap Hasil Belajar Siswa Kelas XI TKJ Mata Pelajaran Teknologi Jaringan Berbasis Luas (WAN) di SMK Negeri 6 Malang - Kembang Regain; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
This research applied quantitative approach and correlational research method in order to find out the influence of peer social support variables and learning discipline on the students learning outcomes in the subject of Wide Area Network (WAN) for students of Grade XI TKJ at SMK Negeri 6 Malang. In doing activities of field industrial practice, students face technical aspects of wired and wireless networks oftentimes. Besides, student understanding of network design and management is still considered as less, due to so this research took WAN subjects as the research area. The data of peer social support and learning discipline were obtained from the results of the questionnaire, while the data of student learning outcomes were obtained from the documentation of research. The study population included 68 students of Grade XI TKJ 2 and XI TKJ 3, SMK Negeri 6 Malang in which they also take parts as research samples (technique of saturation sampling). The classic assumption trial was performed firstly and the results of research data were normally distributed, linear and there were no symptoms of multicollinearity, and also the heteroscedasticity did not occur, so that the parametric statistical approach was applied in the data analysis. Thereafter, regression, correlation, and hypothesis tests were used in analyzing the data. The results showed that there was no influence from peer social support variables and learning discipline toward student learning outcomes, which meant that H0 was accepted. Whereas, the results of the regression significance numbers of the research variables partially or simultaneously obtained successive results of 0.241> 0.05; 0.117> 0.05; 0.233> 0.05.